[D-Ala2, D-Leu5] Enkephalin Attenuates Hepatic Ischemia–Reperfusion Injury in Cirrhotic Rats - Jueying Liu (Frontiers in Surgery, 2022)
Background and AimsHepatic ischemia–reperfusion injury (IRI) is a common phenomenon that occurs after liver transplantation and liver tumor surgery. It can cause liver dysfunction and recovery failure after liver surgery, even leading to acute liver failure. Our aim is to investigate the protective effect and related potential mechanism of [D-Ala2, D-Leu5] enkephalin (DADLE) treatment on hepatic IRI in cirrhotic livers of rats.MethodsThe models of liver cirrhosis and hepatic IRI were established with male Sprague–Dawley rats. DADLE at a dose series of 0.5, 1, or 5 mg·kg−1 was injected intravenously to rats 10 min prior hepatic ischemia, followed by a 6- h reperfusion. The serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), histological changes, and liver cell apoptosis were used to assess liver IRI. The optimal dose of DADLE was assessed by using the Suzuki score and ALT and AST levels. We repeated the hepatic IRI procedure on the optimal dose of the DADLE group and the delta opioid receptor (DOR) antagonist natrindole hydrochloride (NTD) injection group. Serum ALT and AST levels, histological staining, hepatic apoptosis, and serum levels of tumor necrosis factor alpha (TNF-α) and interleukin 1 β (IL-1β) were measured. The expression of protein kinase B (Akt) and its downstream proteins were evaluated by using quantitative real-time polymerase chain action (qRT-PCR) and Western blotting.ResultsCompared with the control group, DADLE treatment at a dose of 5 mg·kg−1 reduced the Suzuki score (mean: 5.8, range: 5.0–6.6 vs. mean: 8.0, range: 7.0–8.9), the ALT level (134.3 ± 44.7 vs. 247.8 ± 104.6), and the AST (297.1 ± 112.7 vs. 660.8 ± 104.3) level. DOR antagonist NTD aggravated hepatic IRI. Compared with the control group, DADLE treatment decreased the number of apoptosis cells and microphages and neutrophils, increased the expression of Akt and its mRNA to much higher levels, and upregulated the mRNA and protein expression of Bcl-2 and Bcl-2-associated death promoter (BAD).ConclusionDADLE treatment at a dose of 5 mg·kg−1 injected intravenously 10 min prior hepatic ischemia could contain rats’ hepatic IRI by activating DOR in cirrhotic livers. The effects of DADLE could be offset by NTD. The potential molecular mechanism seems to be involved in the phosphatidylinositol-3-kinase (PI3K)/Akt pathway.